Self-Efficacy dalam Olahraga: Kajian Bibliometrik: Identifikasi Kontributor Utama dan Arah Perkembangan Penelitian Self-Efficacy dalam Olahraga melalui Pendekatan Bibliometrik - Wulan, Nabella Ayu; Bintari, Dini Rahma (Institut Teknologi Bandung, 2025)
Objectives of this study are to map the historical developments, major trends, academic collaborations, and dominant themes in self-efficacy research in the field of sports and physical activity from 1982 to 2025. This study also identifies key contributors and future research directions using a bibliometric approach. Methods Data were collected from the Scopus and Web of Science databases using relevant keywords such as